Antioxidant Herbs Supplementation Inhibits Endometriosis Extension in Mice - Yuli Trisetiyono (Diponegoro University, 2019)
Background: Increased oxidative stress causes inflammation and increases angiogenesis. It presumed to promote the proliferation of endometriosis tissue. Kebar grass (Biophytum petersianum) and other herbs such as green tea and Cucumis melo, which contain high antioxidants, are expected to decrease oxidative stress, inflammation, angiogenesis, and reduced endometriosis implants.